In Vitro Antioxidant and Antimicrobial Properties of Composite Flour Formulations Developed Using Selected Local Grain Varieties - T. P. Sathsara S. Perera; Pahan I. Godakumbura; M. A. B. Prashantha; S. B. Navaratne (International Journal of Food Science)
The aim of this study was to determine the in vitro antioxidant potential of four extruded and domestically prepared composite flour formulations developed by composting selected locally available grain varieties in Sri Lanka. The potential of the flour extracts to scavenge free radicals were evaluated by performing DPPH, ABTS, and FRAP assays. Furthermore, the antimicrobial activities of the flour formulations against selected Gram-positive and Gram-negative pathogenic microorganisms were comparatively evaluated using agar well diffusion and disk diffusion assays. Ethanol and water extracts of the samples were evaluated for their antimicrobial potential. The results showed that extruded samples possessed high antioxidant properties than samples prepared using the conventional cooking. Furthermore, the antioxidant potential of the formulations evaluated using different assays was strongly correlated. Moreover, the formulations reported positive antimicrobial potential against tested Gram-negative and Gram-positive bacteria. The ethanol extracts of flour formulations exhibited higher susceptibility to tested microbes than that of water extracts while agar well diffusion resulted significantly high inhibition against pathogenic bacteria than that of agar disk diffusion method (p<0.05). In overall, the highest inhibition zone of 17.64 mm was depicted by F4 against Salmonella, while the lowest diameter of 6.09 mm was depicted by F1 against Listeria. In conclusion, the developed flour formulations contained natural antimicrobial agents which can combat common food spoilage and pathogenic bacteria and can be promoted as value-added products with health benefits beyond nutrition.